Targeting Ergosterol Biosynthesis in Leishmania donovani: Essentiality of Sterol 14alpha-demethylase - McCall, Laura-Isobel (PLoS Negl Trop Dis, 2015)
Leishmania protozoan parasites (Trypanosomatidae family) are the causative agents of cutaneous, mucocutaneous and visceral leishmaniasis worldwide. While these diseases are associated with significant morbidity and mortality, there are few adequate treatments available. Sterol 14alpha-demethylase (CYP51) in the parasite sterol biosynthesis pathway has been the focus of considerable interest as a novel drug target in Leishmania. However, its essentiality in Leishmania donovani has yet to be determined. Here, we use a dual biological and pharmacological approach to demonstrate that CYP51 is indispensable in L. donovani. We show via a facilitated knockout approach that chromosomal CYP51 genes can only be knocked out in the presence of episomal complementation and that this episome cannot be lost from the parasite even under negative selection. In addition, we treated wild-type L. donovani and CYP51-deficient strains with 4-aminopyridyl-based inhibitors designed specifically for Trypanosoma cruzi CYP51. While potency was lower than in T. cruzi, these inhibitors had increased efficacy in parasites lacking a CYP51 allele compared to complemented parasites, indicating inhibition of parasite growth via a CYP51-specific mechanism and confirming essentiality of CYP51 in L. donovani. Overall, these results provide support for further development of CYP51 inhibitors for the treatment of visceral leishmaniasis.